31 Effect of cntnap2 polymorphisms on cerebral response to human voice perception and handedness: an fmri study. Issue 8 (13th July 2017) - Koeda, Michihiko; Watanabe, Atsushi; Tsuda, Kumiko; Matsumoto, Miwako; Ikeda, Yumiko; Kim, Woochan; Tateno, Amane; Naing, Banyar Than; Karibe, Hiroyuki; Shimada, Takashi; Suzuki, Hidenori; Matsuura, Masato; et al.
Abstract : Objective: Contactin-associated protein-like2 (CNTNAP2) is one of the risk markers in the pathogenesis of language impairment and thought disturbance, such as autism spectrum disorders and schizophrenia. Although recent neuroimaging studies have demonstrated that CNTNAP2 polymorphisms affect left-hemispheric function of language processing, no study has investigated the influence of these polymorphisms on right-hemispheric function involved in human voice perception, and handedness. We investigated whether CNTNAP2 polymorphisms (rs7794745 and rs2710102) affect voice-specific brain function and handedness. Method: One hundred and eight healthy Japanese volunteers (74 right-handed and 34 non-right-handed) had their brain function examined while they were passively listening to reverse sentences (rSEN), identifiable non-vocal sounds (SND), and sentences (SEN). The study protocol was approved by Ethics Committee. After complete explanation of the study, written informed consent was obtained from all subjects. Data analysis of fMRI was performed with statistical parametric mapping software SPM8. Genomic DNA samples were extracted from peripheral blood using standard procedures. Since these SNPs are known as biological high-risk markers for ASD, epilepsy, mental retardation, schizophrenia, and cognitive impairment, we investigated the genotype of brain function in these 2 SNPs: (rs7794745 and rs2710102) in CNTNAP2. The genotyping of all subjects was determined in comparison with control DNA confirmed by sequencing in the SNP pattern. Genotype of rs7794745 is A/A, A/T, and T/T; that of rs2710102 is G/G, G/A, A/A. The genotypes were classified into A/A and A/T in rs7794745, and G/G and A carriers (G/A and A/A) in rs2710102, respectively. Results: In full factorial design analysis, rs7794745 (A/A or A/T) × rs2710102 (G/G or A carrier (A/G and A/A)) × voice-specific response (rSEN or SND), the main effect of rs7794745 (A/A or A/T) was significantly revealed at the right middle frontal gyrus (MTG) and bilateral superior temporal gyrus (STG). This result suggests that rs7794745 genotype impacts on voice- specific brain function. Furthermore, interaction effect was significantly observed among MTG-STG activations by human voice perception, rs7794745 (A/A or A/T), and handedness. Conclusion: CNTNAP2 polymorphisms could be one of the remarkable biomarkers verifying genetic influence in voice-specific brain function and handedness in psychiatric disorders.